Strategy for reduction of medical costs and growth of the healthcare industry after establishment of the national health insurance system in Japan: lessons for the Indonesian health care reform system -II- (Medical Journal of Indonesia, 2014)
Japan has long operated a government-based health insurance system covering the entire population, and has been focusing on strategies for balancing viable national health care services with the need to minimize national health care expenditure. Hemodialysis (HD) is a representative form of medical treatment that is expected to expand in Indonesia in the near future, and which will require sustained financial support from the national health insurance system. In this report, consecutive to our previous one, we describe how the Japanese government has attempted to minimize medical expenditure in the past, focusing especially on HD.